An investigation of the prevalence of musculoskeletal disorders, dynamic balance, endurance of trunk flexor and spine extensors muscles, and core muscles strength among the flight staff - V Sobhani; V Mazloum; A Khatibiaghda; A Shakibaie (فصلنامه ابن سینا, 2015)
Background: Poor physical fitness and subsequent musculoskeletal disorders are the major reasons for absence from work and decrease in occupational quality among flight staff. Therefore, the purpose of this study was to investigate the prevalence of musculoskeletal disorders and assessment of some physical fitness factors in flight staff.